2004
DOI: 10.1111/j.1348-0421.2004.tb03628.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Competition of Macrolide‐Resistant and ‐Susceptible Helicobacter pylori Strains

Abstract: Abstract:We examined population dynamics in a mixed culture of clonally related macrolide-resistant and -susceptible Helicobacter pylori strains isolated from a single patient. The resistant strain had a macrolide resistance-conferring A2143G mutation in the 23S rRNA gene. The growth rate of these two strains did not apparently differ when cultured separately. On the other hand, by conducting sequential passage of a mixed culture of the resistant and the susceptible strains, the ratio of the resistant strain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The association between macrolide resistance and a significant burden on bacterial fitness was also observed in other bacteria. When a sequential passage of a mixed culture between macrolide-resistant and macrolidesusceptible Helicobacter pylori was performed, the ratio of the resistant strain to the susceptible strain was considerably reduced per passage (31). It was also shown that clarithromycin resistance confers a fitness cost on H. pylori in mice and the fitness cost was reduced in clinical isolates (9).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The association between macrolide resistance and a significant burden on bacterial fitness was also observed in other bacteria. When a sequential passage of a mixed culture between macrolide-resistant and macrolidesusceptible Helicobacter pylori was performed, the ratio of the resistant strain to the susceptible strain was considerably reduced per passage (31). It was also shown that clarithromycin resistance confers a fitness cost on H. pylori in mice and the fitness cost was reduced in clinical isolates (9).…”
Section: Discussionmentioning
confidence: 91%
“…Even though many types of antibiotic resistance impose a biological cost on bacterial fitness, the fitness cost can be reduced at different levels through compensatory mutations (5,10,11,33,40). In addition, some resistance-conferring mutations or determinants do not incur an apparent fitness burden or even enhance the fitness of the antibiotic resistant strains (10,26,31,37,38,44). For example, a modeling study on antibiotic resistance revealed that some resistant bacteria, such as penicillin-resistant strains, did not show a decreased fitness in the host; instead, these resistant strains possessed an increased ability to transmit between hosts compared to the susceptible strains (6).…”
mentioning
confidence: 99%
“…The population and the ratio of the resistant and susceptible strains in the culture were measured at the 0, 3rd, 6th, and 10th passages. 16 Pairwise competition experiments to assay relative fitness A standard competition assay developed for E. coli by Levin et al was adapted for Campylobacter jejuni as follows 19 : approximately equal densities of the Cj-R and their ancestral Cj-S were paired and mixed in 10 ml MH broth at a dilution of 1:200. These cultures were grown to stationary phase, and the relative densities of each type of bacterium were then estimated by plating on nonselective media.…”
Section: Population Dynamics Of the Resistant And Susceptible Strainsmentioning
confidence: 99%
“…Kanai et al. showed that the 23S rDNA A2143G mutation conferring macrolide resistance did not have impact on the growth rate, but when a mixture of resistant and susceptible strains was subcultured, they observed a decrease in the proportion of the resistant strain indicating an advantage for the susceptible strain [7]. A method of PCR–SSCP (polymerase chain reaction–single strand conformation polymorphism) followed by sequence analysis was applied with success to detect the mutations leading to macrolide resistance in Japan.…”
Section: Culturementioning
confidence: 99%